Comparative Risk Evaluation of Contaminant Intrusion in Water Distribution Networks via Complex Network Analysis - Jordana Alaggio; Daniel Bezerra Barros; Bruno Brentan; Gustavo Meirelles (Engineering Proceedings)
Water distribution networks (WDNs) aim to ensure uninterrupted delivery of high-quality water; however, they are susceptible to failures that can compromise water quality. Decision-makers need to pinpoint crucial network components to optimize maintenance and improve system efficiency. This research investigates the risks of contaminant intrusion in WDNs. Complex network theory (CNT) provides an alternative approach by modeling WDNs as complex networks and analyzing network dynamics, contaminant propagation, and critical elements. EPANET software simulates contamination, while CNT metrics assess node influence. Our findings demonstrate the compatibility and potential hybrid form to work with these methodologies, offering a more efficient approach to WDN risk management.